2011
DOI: 10.1108/14714171111175882
|View full text |Cite
|
Sign up to set email alerts
|

User‐driven innovation in a construction material supply network

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The nature of value-creation relies on the approach we take toward it; if the customer is invited to participate in the cocreation process, it is the firm that creates value for customer (Zwass, 2010). Therefore, co-creation is defined as developing new products and services in a quicker and more relevant and innovative way than traditional processes which it brings about an opportunity for continued interaction between the firm and customers and the firm is willing to work with external stakeholders (Wandahl et al, 2011;Sawhney, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The nature of value-creation relies on the approach we take toward it; if the customer is invited to participate in the cocreation process, it is the firm that creates value for customer (Zwass, 2010). Therefore, co-creation is defined as developing new products and services in a quicker and more relevant and innovative way than traditional processes which it brings about an opportunity for continued interaction between the firm and customers and the firm is willing to work with external stakeholders (Wandahl et al, 2011;Sawhney, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This would in total benefit the general Danish welfare with 1.3 billion US$. From this it can be concluded that an unexploited potential for improvement exists (Wandahl et al 2011). There are several reservations to take when concluding on comparative analysis of productivity, but the tendency is clear. Since 1980 the productivity development in the international building industry has not been overwhelming.…”
Section: Industrialization In Buildingmentioning
confidence: 79%
“…For example, Kadefors (2004) mentions workshops held at the beginning of construction projects as a means to agree on common objectives and working methods and to create trust. Additionally, Wandahl et al (2011) suggests that sharing an interest for providing end-users with appealing and usable products may help the network establish closer collaboration and increased competitiveness as the end-users are one of the main aspects the network partners have in common.…”
Section: Role Descriptionmentioning
confidence: 99%